Perilaku merokok pasien jantung koroner: studi di rumah sakit Saras Husada - Debsy Vonneke Pattilima; Anggoro Budi Hartono; Trisno Agung Wibowo (Berita Kedokteran Masyarakat (BKM), 2017)
Smoking behavior of patients with coronary heart diseases: a study in the Saras Husada hospitalPurposeThis study aimed to examine the determinants of smoking behavior in patients with coronary heart disease (CHD) in Saras Husada hospital Purworejo.Methods A cross sectional study was conducted involving 205 respondents. Dependent variable was smoking behavior in patients with coronary heart diseases, while independent variables were knowledge about dangers of smoking, exposure to cigarette advertising and smoking behavior of family members with confounding variables: age, sex, and education. Data were collected through interviews using a structured questionnaire and analyzed using bivariate and multivariate tests.ResultsThis study found no correlation of cigarette advertisement exposure, smoking behavior of family members, gender, and education with smoking behavior in CHD patients. Multivariate analysis showed that gender variables influence the determinant of smoking behavior in CHD patients.ConclusionThis study provides knowledge that gender is the strongest determinant affecting smoking behavior in CHD patients. It is necessary to apply the local regulation ban on smoking, especially for men in public places, workplaces and schools.